New Methods for Solving the Problem of Radiation and Propagation of Electromagnetic Waves (Global Journal of Science Frontier Research, 2018)
The history of the establishment of the laws of electrodynamics counts already more than 200 years, but, in spite of this, physics of the emission of electromagnetic waves up to now so is not explained and there are only phenomenological laws, which they use, until now. As the basis of such laws is assumed the concept of the vector potential of magnetic field, which follows from the phenomenological Ampere law, which is established on the basis empirical laws about power interaction of the current carrying systems. In the article it is shown that physical nature of electromagnetic waves is obliged to the dependence of scalar potential on the speed. This approach gives the possibility to introduce into the electrodynamics new concept-the scalar-vector potential of the moving charge, which determines all dynamic laws of electrodynamics.
Keywords: magnetic field; vector potential; electromagnetic wave; the laws of self-induction; wave equation; telegraphic equations; scalarvector potential